Nilai Pendidikan Karakter dalam Film Wish Dragon Produksi Sony Pictures - Abdullah Zaid Zarkasyi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The purpose of this research is to determine the value of character education in the film wish dragon. The method used by the author is a qualitative descriptive method. And the analysis technique used is to collect data about the film scenes to find out the moral values contained in the film. The research results obtained from the analysis of moral value education in the wish dragon film show that this film reflects many moral values, and to help children socialize well means it can be used to teach moral values.